The Rhizophagus irregularis permease RiFTR1 functions without a ferroxidase partner for reductive iron transport - Elisabeth Tamayo; Víctor Manuel López-Lorca; Chaeeun Shim; Olga López-Castillo; Araceli G. Castillo; Natalia Requena; J. Philipp Benz; Nuria Ferrol (Scientific Reports)
Abstract The contribution of arbuscular mycorrhizal fungi (AM fungi) to plant iron (Fe) acquisition has been demonstrated in several studies. A previous investigation revealed that the AM fungus Rhizophagus irregularis utilizes a high-affinity reductive pathway for Fe uptake, mediated by the Fe transporter RiFTR1. In this study, we used a genome-wide approach in R. irregularis to find genes encoding ferroxidases of the multicopper oxidase (MCO) gene family in an attempt to identify the ferroxidase partner of RiFTR1. Nine genes putatively encoding MCOs (RiMCO1-9) were identified. Yeast complementation assays demonstrated that RiMCO1 and RiMCO3 can function as ferroxidases, suggesting their involvement in the reductive Fe uptake pathway. Surprisingly, RiFTR1 was capable of transporting Fe in yeast without a ferroxidase partner, resembling the Fe transport mechanism of plant IRT1-like systems. RiFTR1 exhibited increase expression in arbuscules. Overexpression of RiFTR1 in Medicago truncatula roots led to enhanced mycorrhizal colonization and arbuscule abundance, highlighting the significance of Fe for AM symbiosis.